Three pillars as new strategy to curb corruption in public procurement in Malaysia - Mohd Yusof, Hairuzaki; Mohd Yusof, Danial; Mohd Adnan, Normala (Universiti Malaysia Pahang Al-Sultan Abdullah, 2025)
Public procurement in Malaysia remains a major avenue for corruption despite existing legal frameworks and digital reforms. This study investigates the necessity for new governmental strategies by analysing three core dimensions: the effectiveness of current laws and procedures, the role of human values and ethics, and the integration of emerging technologies. Using qualitative methods, data were collected through semi-structured interviews with 15 experts and 7 incarcerated individuals involved in procurement-related offences. These primary findings were supported by secondary data from selected Malaysian Anti-Corruption Commission case files. Ethical clearance was obtained, ensuring participant confidentiality, informed consent, and voluntary participation. The study adhered to strict ethical protocols to enhance the credibility and trustworthiness of the data. Findings reveal a critical need for reforms in legislative enforcement, governance culture, and digital infrastructure. Specifically, weaknesses in law implementation, ethical breaches among procurement actors, and the slow adoption of digital monitoring tools were identified as persistent vulnerabilities. The analysis underscores the urgency of a holistic and sustainable anti-corruption strategy based on three interrelated pillars: strengthening legal frameworks, cultivating ethical leadership and values, and leveraging digital technologies and data analytics. The study recommends that these pillars form the basis of a new, adaptive strategy to effectively curb and combat corruption in public procurement. A cross-sectoral commitment involving government, civil society, and digital innovation is vital to build resilience against corruption and promote integrity within Malaysia’s procurement system